(untitled) (BIS Humanities and Social Science, 2026)
This research analyzes the role of the Lemah Urip Community in Karanganyar Pottery Village as an autonomous Change Agent in diffusing a culture-based Social Enterprise Model amid sub-optimal village institutional capacity. Karanganyar Pottery Village is renowned as a center for traditional pottery crafts that has existed for generations and serves as an educational tourism destination. This context is marked by an urgent need for consistent driving actors and a lack of optimal institutional sustainability. The study employs the framework of Development Communication and the Diffusion of Innovation Theory to address the issue of sustainable development, which has become a transformative global agenda. For development to be inclusive and participatory, a planned communication approach is essential. This is where the central role of Development Communication is needed. This descriptive qualitative research uses a case study method, where primary data was obtained through in-depth, direct interviews with the Head of Lemah Urip, Board Members, and Sanggar Children (Studio/Workshop Participants), and verified using the Source Triangulation technique. The results indicate that Lemah Urip successfully disseminated the Social Enterprise innovation through intense and credible interpersonal communication channels. Adoption success was driven by the innovation’s clear Relative Advantage and Observability demonstrated through the Art Studio (Sanggar Seni). Existing resistance was overcome by the active involvement of the younger generation (Sanggar Children) as pioneers who bridged communication. The conclusion of this study confirms that a community’s communication structure, utilizing a development communication approach, can function effectively in encouraging innovation adoption and rural development sustainability.